Active phagocytosis of Mycobacterium tuberculosis (H37Ra) by T lymphocytes (Jurkat cells). Issue 2 (August 2015) - Zhang, Min; Zhu, Qi; Shi, Ming; Liu, Yang; Ma, Lei; Yang, Yining; Feng, Dongyun; Dai, Wen; Zhang, Lin; Kang, Tao; Chen, Ping; He, Ying; et al.
Highlights Jurkat T lymphocytes were co-cultured with the inactivated Mtb H37Ra. The Jurkat T lymphocytes could actively phagocytize the inactivated Mtb. The remodeling of actin played an important role in the macropinocytotic process. The complements inside the serum could regulate the phagocytosis.